Information technology and telecommunications: A course on the World Wide Web - McGreal, Rory (Journal of Distance Education, 1998)
The East-West project has been designed to provide Canadian adult learners and particularly learning professionals with the opportunity to complete a full course online through the World Wide Web (WWW). Four Canadian provinces (Alberta, British Columbia, New Brunswick, and Newfoundland) participated in examining different approaches to implementing accredited programs for adults that would be accessible in the workplace, at home, in schools, and in community centres using the WWW. The project is an example of interprovincial collaboration, resource sharing, and credit acceptance. The experience has also been used to develop the necessary design expertise and set common standards in Web-based course development. The course is being used to promote new ways of learning, produce effective learning materials, and provide innovative approaches to teaching. Another advantage is that teachers and designers can keep materials current. Currency and relevancy can be maintained through the development of internationally recognized open standards for instructional design, pedagogy, courseware, visual interfaces, and cybernavigation. Teachers and designers can make use of authoring standards and templates that have been developed for this project. They are available in the appendix or at the TeleEducation NB web site: http://teleeducation.nb.ca/. Industry Canada